Transistors: Layer‐by‐Layer Assembled 2D Montmorillonite Dielectrics for Solution‐Processed Electronics (Adv. Mater. 1/2016). Issue 1 (January 2016) - Zhu, Jian; Liu, Xiaolong; Geier, Michael L.; McMorrow, Julian J.; Jariwala, Deep; Beck, Megan E.; Huang, Wei; Marks, Tobin J.; Hersam, Mark C.
Abstract : Layer‐by‐layer assembled 2D montmorillonite nanosheets are employed by M. C. Hersam and co‐workers for high‐performance, solution‐processed dielectric thin films, as described on page 63. These spatially uniform sub‐10‐nm‐thick dielectrics possess high areal capacitances and low leakage currents that enable low‐voltage operation of complementary solution‐processed semiconductor transistors. These results are likely to impact ongoing efforts to realize large‐area flexible and wearable electronics via scalable additive manufacturing.